Bioengineered Human Stromal Lenticule for Recombinant Human Nerve Growth Factor Release: A Potential Biocompatible Ocular Drug Delivery System - Leonardo Mastropasqua; Mario Nubile; Giuseppina Acerra; Nicola Detta; Letizia Pelusi; Manuela Lanzini; Simone Mattioli; Manuela Santalucia; Laura Pietrangelo; Marcello Allegretti; Harminder S. Dua; Jodhbir S. Mehta; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Small incision lenticule extraction (SMILE), is a surgical procedure for the myopia correction, during which a corneal stromal lenticule is extracted. Given that we have previously demonstrated how this discarded tissue could be repurposed as a bio-scaffold for stromal engineering, this study aimed to explore its use as an ocular drug delivery system of active molecules, using neurotrophic factor Nerve Growth Factor (NGF). We employed human stromal lenticules directly collected from healthy donors undergoing SMILE. Following a sodium dodecylsulfate (SDS) treatment, decellularized lenticules were incubated with a suspension of polylactic-co-glycolic-acid (PLGA) microparticles (MPs) loaded with recombinant human NGF (rhNGF-MPs). Fluorescent MPs (Fluo-MPs) were used as control. Data demonstrated the feasibility to engineer decellularized lenticules with PLGA-MPs which remain incorporated both on the lenticules surface and in its stromal. Following their production, the in vitro release kinetic showed a sustained release for up to 1 month of rhNGF from MPs loaded to the lenticule. Interestingly, rhNGF was rapidly released in the first 24 h, but it was sustained up to the end of the experiment (1 month), with preservation of rhNGF activity (around 80%). Our results indicated that decellularized human stromal lenticules could represent a biocompatible, non-immunogenic natural scaffold potential useful for ocular drug delivery. Therefore, combining the advantages of tissue engineering and pharmaceutical approaches, this in vitro proof-of-concept study suggests the feasibility to use this scaffold to allow target release of rhNGF in vivo or other pharmaceutically active molecules that have potential to treat ocular diseases.